Students' Intensity in Watching English Program Television and Its Influence on Their Competence in English Vocabulary - Atunnisa, Fauzi; Abrar, Mukhlas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article explores effective strategies for enhancing English vocabulary, crucial for academic success and communication proficiency. Utilizing a qualitative research methodology, the study investigates the impact of exposure to television series on the vocabulary acquisition of eleventh-grade students at MAS AS’AD Jambi during the 2023/2024 academic year. Data were collected through questionnaires administered to a sample consisting of one class of 33 students from the tenth-grade cohorts in Science (IPA), Social Studies (IPS), and Islamic Education (PAI). The findings suggest that extensive exposure to television series significantly enhances students' vocabulary in terms of both meaning and structure. Furthermore, the results indicate that students who received vocabulary pre-teaching generally outperformed their peers, regardless of the language of the on-screen texts. The study concludes that television shows can substantially boost students' vocabulary skills, offering valuable insights for educational strategies in language acquisition.